Pengetahuan dan Perilaku Merokok pada Pasien Hipertensi - Nainggolan, Citra Wachyuni; Siagian, Ernawaty (Journal of Telenursing (JOTING), 2024)
This study aims to examine the relationship between the level of knowledge and smoking behavior in hypertensive patients at the Bandar Lampung Adventist Hospital. This research is a simple descriptive quantitative research. The results of the study showed that the relationship between knowledge and smoking behavior in hypertensive patients at Bandar Lampung Adventist Hospital had a significance value of 0.047 (p <0.05) and r = 0.272, which means there was a relationship between knowledge and smoking behavior and smoking behavior in patients at the hospital. Bandar Lampung Adventist. In conclusion, a person's knowledge has a significant relationship with the smoking behavior of patients with hypertension. Keywords: Hypertension, Knowledge, Smoking Behavior